2012
DOI: 10.1111/j.1365-277x.2012.01291.x
|View full text |Cite
|
Sign up to set email alerts
|

Energy balance in haemodialysis and peritoneal dialysis patients assessed by a 7‐day weighed food diary and a portable armband device

Abstract: HD and PD patients have a negative EB and are at risk of malnutrition. Inflammatory status determines a lower EI per day and a reduction in TEE per day. The most important parameter in determining EB in HD and PD patients is EI per day. This topic deserves further investigation to better understand the mechanisms of impaired EB with respect to preserving patients' nutritional status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 56 publications
2
3
0
Order By: Relevance
“…In our study there was significant negative correlation between basal metabolic rate and CRP with p-value 0.018. In agreement with our results Bovio et al, [24] .…”
Section: Discussionsupporting
confidence: 94%
“…In our study there was significant negative correlation between basal metabolic rate and CRP with p-value 0.018. In agreement with our results Bovio et al, [24] .…”
Section: Discussionsupporting
confidence: 94%
“…The NKF-KDOQI guidelines recommend that at least 50% of the dietary protein should be of high biological value for patients with PD (26). Recent studies reported that negative nitrogen and energy balance according to low intake of protein and energy in PD patients (25,27). Similarly in this study, all of patients could not reach the dietary energy and protein intake recommendations for PD patients but fat intake was found high.…”
Section: Discussionsupporting
confidence: 40%
“…Patients need to be followed up regularly in order to avoid misreporting [26]. The 7DWR has been used in patients on dialysis in a previous study [27]. The study showed that the macronutrient and micronutrient intakes for patients on HD and PD are largely inadequate compared to the K/DOQI of the US National Kidney Foundation and the Italian LARN recommendations, confirming that reduced DEI as well as an unbalanced diet are among the main risk factors of malnutrition in these patients [3,27].…”
Section: Discussionmentioning
confidence: 99%
“…The 7DWR has been used in patients on dialysis in a previous study [27]. The study showed that the macronutrient and micronutrient intakes for patients on HD and PD are largely inadequate compared to the K/DOQI of the US National Kidney Foundation and the Italian LARN recommendations, confirming that reduced DEI as well as an unbalanced diet are among the main risk factors of malnutrition in these patients [3,27]. Highlights of the current study are that if patients are appropriately trained and motivated and if doubts are clarified during data collection, weighed dietary records can give very accurate estimates of nutrient intakes.…”
Section: Discussionmentioning
confidence: 99%